How to motivate yourself and others? Intended and unintended consequences. (2015) - Schroeder, Juliana; Fishbach, Ayelet
Abstract: To achieve goals, individuals and organizations must understand how to effectively motivate themselves and others. We review three broad strategies that people employ to increase motivation: giving feedback, setting goal targets, and applying incentives. Although each of these strategies can effectively motivate action under certain circumstances and among certain people, they can also result in unintended consequences: not helping or even hurting motivation. For example, employers may give positive feedback that leads employees to relax their effort or negative feedback that undermines employees' commitment, organizations may set goals that are overly ambitious and consequently reduce motivation, and certain incentives might appear attractive before pursuing an action but uncertain incentives better motivate action during goal pursuit. By identifying when and how these common motivational strategies work versus fail, we are able to prescribe a specific set of guidelines that will help people understand how to motivate themselves and others.